1983
DOI: 10.1115/1.3266381
|View full text |Cite
|
Sign up to set email alerts
|

Blade Configurations and Performance of the Savonius Rotor With Application to an Irrigation System in Indonesia

Abstract: This paper describes results of a systematic wind tunnel study aimed at development of the wind-operated irrigation system suitable for meeting needs of small farms in Indonesia. Using several models of the single-stage Savonius configuration, influence of the blade gapsize and overlap on the output is assessed and their favourable combination established for a given blade geometry. This is followed by the performance data on a larger, self-starting, two-stage model operating in conjunction with several differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…INTRODUCTION 1 As fossil fuels continue to decrease, leading to an energy crisis, the demand for sustainable energy sources is *Corresponding Author Email: aramiar@nit.ac.ir (A. Ramiar) growing. In the past decade, there has been a push for immediate and effective solutions to the climate of world challenges.…”
Section: Nomenclaturementioning
confidence: 99%
See 1 more Smart Citation
“…INTRODUCTION 1 As fossil fuels continue to decrease, leading to an energy crisis, the demand for sustainable energy sources is *Corresponding Author Email: aramiar@nit.ac.ir (A. Ramiar) growing. In the past decade, there has been a push for immediate and effective solutions to the climate of world challenges.…”
Section: Nomenclaturementioning
confidence: 99%
“…The Savonius rotor has various uses, such as powering an electric generator, ventilating spaces, and stirring water to prevent the formation of ice in pools during the winter months. These applications have been explored in previous research (1,2). Initial research has demonstrated promising starting characteristics for twisted blades.…”
Section: Nomenclaturementioning
confidence: 99%
“…The Savonius rotor can be used for pumping water, driving an electrical generator and agitating the water to keep stock ponds ice-free during the winter. It can be used in buildings for heating, ventilation, and air-conditioning (HVAC) purposes, [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The geometric factors that influence the performance of the Savonius rotor are aspect ratio, separation gap, overlap, end/deflecting plates, shielding, and number of blades [1][2][3][4][5][6]. It has been found from investigation that shielding the returning blades of the rotor reduces the negative torque drastically, yet at the expense of complexity, since the shielding must be placed with regard to the direction of the wind.…”
Section: Introductionmentioning
confidence: 99%